Exploring clients’ meta-comments in psychotherapy using conversation analysis - Burdett, Mark (2018)
Asking clients about shifts in their moment-to-moment experience - for example, when they laugh, smile or make a comment to themselves - is done in a variety of different ways in different therapeutic approaches. However, the various therapies do not necessarily specify what might be happening for the client when a shift occurs, and are instead more interested in the therapist’s response to those events. Method of Levels (MOL) therapy does however, make a series of claims about what is occuring for the client during those shifts, termed ‘disruptions’. Disruptions are proposed to be short responses, offering comments on a client’s own talk, which are not spontaneously elaborated on. Asking about disruptions in MOL is one of the two over-arching goals of the therapy (Carey, 2006). As MOL emphasises these disruptions so heavily, instances when shifts occured during clients’ talk were assessed against MOL’s proposals.